Analysis of Policy Implementation of the Food Program in Rural Areas - Firdasari, Kama Astrid; Hardjati, Susi (Journal La Sociale, 2024)
In order to reduce poverty rates, the Ministry of Social Affairs through the Basic Food Program aims to reduce the burden on KPM expenditures by fulfilling part of their food needs as well as reducing poverty. Implementation of this policy was also held in Purisemanding Village, Jombang Regency. However, it is not yet known how far the Basic Food Program has been implemented in these rural areas. The aim of this research is to analyze the implementation of the Basic Food Program in rural areas, especially in Purisemanding Village. This research uses research methods descriptive with a qualitative approach. By using data analysis techniques developed by Miles & Huberman. The research focus refers to Matland's (1995) theory, namelyPolicy Accuracy, Implementation Accuracy, Target Accuracy, and Environmental Accuracy. The results of the research conclude that the accuracy of the Basic Food Program policy has been implemented well but has not been able to reduce the poverty rate, the accuracy of implementation has been carried out well by the policy implementing agency, however the accuracy of the target has been good but has not been implemented optimally, especially in terms of infrastructure, and environmental accuracy is also lacking. carried out optimally, especially for the external environment.